Good governance of social entrepreneurship from Maqasid Al-Shari’ah - Ismail, Yusof; Mhd. Sarif, Suhaimi; Azan, Zaliza (Zes Rokman Resources, 2017)
The study explores the management of good governance of social entrepreneurship from Maqasid al-Shariah perspectives. Management of good governance of social entrepreneurship from Maqasid al-Shariah implies moderation (wasatiyyah). This framework allows social entrepreneurship with profit and non-profit agenda to be managed with moderate approach of Maqasid al-Shariah. The regulatory framework under traditional maqasid is perceived to be of rigid and reduces flexibility and the hybrid model of corporate entities in social entrepreneurship. Wasatiyyah enables moderate guidelines, just and balanced in formulating, executing and evaluating strategies, plans, and activities. The presence of wasatiyyah of Maqasid al-Shariah is apparent in Malaysian economic contexts have incorporated the essence of wasatiyyah through the consistent objectives to eradicate poverty, maintain national unity and increase wealth of the nation. Theoretically, good governance with Maqasid al-Shariah and wasatiyyah approaches allows flexible and focused for all enterprises to perform better. Social entrepreneurship with the hybrid corporate objectives require corporate governance with Maqasid al Shariah regulatory framework and wasatiyyah approach.